Narrative research into the possibilities of classroom-generated stories in english teacher education (2015)
This paper summarizes a narrative inquiry carried out with forty volunteer undergraduate participants attending the course Overall Communication, in the English Teacher Education Program in the School of Humanities of the Universidad Nacional de Mar del Plata, Argentina. It addresses their family/academic identities and personal practical knowledge—as articulated in their written narratives about a class activity concerning the telling of “unheroic” lives—produced by these students while exploring heroes in Irish films. Narrative interpretation of these undergraduates’ work yields categories of analysis concerning story protagonists’ origins, moral values, types of knowledge generated, and implications for English teacher education. Finally, the paper discusses some issues its findings raise in this field.Este artículo resume una indagación narrativa realizada con cuarenta estudiantes voluntarios del curso Comunicación Integral del Profesorado de Inglés en la Facultad de Humanidades de la Universidad Nacional de Mar del Plata, Argentina. Aborda identidades familiares/académicas y el conocimiento práctico personal —manifestados en narrativas escritas sobre una actividad en clase acerca de vidas “no heroicas”— que surgen tras explorar héroes en películas irlandesas. La interpretación narrativa de los relatos arroja categorías de análisis sobre los orígenes de los protagonistas no heroicos, los valores morales emergentes, los tipos de conocimiento generados y sus posibilidades en la formación docente inicial en idioma inglés. Finalmente, el trabajo discurre sobre algunas implicancias de sus resultados en este campo de la formación del profesorado.